Endoscopic treatment of vesicoureteric reflux in paediatric patients:results of a long-term study - Scarpa, A. A.; Rossi, C. D.; Casolari, E.; Gatti, C. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim of the work: Vesicoureteric reflux is the most common uropathy in paediatric age. It may be treated with open surgery, antibiotic therapy or endoscopic injection. The purpose of this work is to determine outcomes and experiences of parents with children who underwent endoscopic treatment for VUR. Materials and methods: In a period of 5 years (from 2004 to 2009) 48 patients (20 boys and 28 girls, mean age 5,5, range 1-17) underwent endoscopic treatment for VUR. Sample included 31 cases of primary reflux (64,6%), 11 complex cases of VUR (6 duplex system, 3 duplex system with ureterocoele, 2 bladder exstrophy) and 6 children (12,5%) with VUR secondary to neurogenic bladder. All procedures were performed by the same surgeon. A questionnaire assessing experiences with endoscopic treatment was administered to all families. Results: Follow-up lasted from a minimum of 6 months to 5 years. Overall cure rate was 68,7% (33/48) per child after a single injection, a second injection performed in cases with VUR recurrence raised it to 81,2% (39/48 patients). Overall cure rate per grade of VUR was 60% (3/5) for grade I, 94,1% (16/17) for grade II,  86,9% (20/23) for grade III, 64,7% (11/17) for grade IV and  85,7% (6/7) for grade V. Minimal postoperative complications were recorded: 2,1% urinary tract obstruction, 12,5% macrohaematuria, 6,2% lumbar pain, 4,1% urinary retention or strangury. The results of the survey given to families were encouraging. Conclusions: Endoscopic treatment for VUR seems to be a feasible procedure as primary intervention.